Spatial Multi-Criteria Analysis and Least-Cost Path on The Highway Route Planning: A Case Study of Bawen – Yogyakarta Highway, Indonesia - Bramantiyo Marjuki; Iwan Rudiarto (Department of Urban and Regional Planning, Diponegoro University, 2020)
Infrastructure planning ideally not only considers the geotechnical aspects and physical conditions of the infrastructure development location but also must be able to support regional development. One kind of spatial analysis technique which has capabilities to integrate various regional characteristics associated with its suitability for a particular use is spatial multi-criteria analysis. By using Bawen-Yogyakarta Toll Road Plan as a case study, this research is intended to apply route planning that takes into account regional characteristics, through the involvement of Spatial Multi-Criteria Analysis, Analytic Hierarchy Process, and Least Cost Path analysis. The analysis results then compared with the government preferred route to see its advantages and disadvantages. The results show that the generated route from the analysis has several advantages over the government preferred route, while also having some shortcomings. The advantages of route analysis results compared to government preference routes include: better able to avoid earthquake and landslide-prone areas, better support to the preservation of protected areas, has more areas with flat to gentle topography, and have smaller additional construction cost as the consequences of intersection with existing roads, rivers and railways, In terms of affected land-use, generated route also has minimum negative impacts on the sustainability of agricultural land in the study area. The shortcomings of the analysis result are: not yet able to avoid flood and volcanic eruptions-prone areas as well as government’s preferences route, higher land acquisition cost estimation, and less support for industrial and tourism activities in the research area. Improvement of analysis methods, data, and cost assessment strategy is needed to obtain better results and more appropriate modeling and analysis, in order to support regional infrastructure planning and development.